Heparin-binding EGF-like growth factor induces heart interstitial fibrosis via an Akt/mTor/p70s6k pathway. - Hong Lian (Public Library of Science (PLoS), 2012)
Heparin-binding epidermal growth factor-like growth factor (HB-EGF) is essential for maintaining normal function of the adult heart and is known to play an important role in myocardial remodeling. In the present study, we observed that heart-specific HB-EGF transgenic (TG) mice had systolic dysfunction with decreased fractional shortening (FS%), increased end-systolic diameter (LVIDs) at 5 months of age, increased heart fibrosis, and increased mRNA expression of Col1α1 and Col3α1 at 1, 3, 5 and 7 months of age compared to nontransgenic (NTG) littermates. However, the left ventricular anterior wall thickness at end-systole (LVAWs) of the TG mice was not different than the NTG mice. Phosphorylation levels of Akt, mTor and p70s6k were increased due to HB-EGF expression in TG mice compared with the NTG mice at 3 and 7 months of age. Additionally, activated Akt, mTor and p70s6k were co-localized with vimentin to cardiac fibroblasts isolated from TG mice. Furthermore, HB-EGF significantly increased phosphorylation levels of Akt, mTor and p70s6k and increased expression of type I collagen in cultured primary cardiac fibroblasts. Rapamycin (Rapa) and CRM197, inhibitors of mTor and HB-EGF respectively, could inhibit the expression of type I collagen in the cultured primary cardiac fibroblasts and Rapa suppressed interstitial fibrosis of the heart tissues in vivo. In addition, a BrdU assay showed that HB-EGF increased proliferation of cardiac fibroblasts by 30% compared with cells without HB-EGF treatment. HB-EGF-induced proliferation was completely diminished in the presence of Rapa. These results suggest that HB-EGF induced heart fibrosis and proliferation of cardiac fibroblasts occurs through activation of the Akt/mTor/p70s6k pathway.